2010
DOI: 10.1007/s10900-010-9311-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Screening and STI Among Detained Youth

Abstract: Our objective was to understand the relationship between mental health screening results, health disparity, and STI risk among detained adolescents. In this 24-month cross-sectional study of 1,181 detainees (age 13-18 years), we examined associations between race, gender, mental health screening results (as measured by the Massachusetts Youth Screening Instrument-2nd Edition) and sexually transmitted infection rates (STI; chlamydia, gonorrhea, and trichomonas). Consistent with previous research, females and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…Also, similar to other recent studies (Aalsma et al, 2011; Archer et al, 2004; Archer et al, 2010; Grande et al, 2012; Grisso et al, 2001; Nordness et al, 2002; Stewart & Trupin, 2003), mean scores were higher for females than males on all subscales except thought disturbance (male only). While prior studies using samples dating from 2000 to 2006 found the Angry/Irritable subscale to be the most highly endorsed subscale with Alcohol/Drug Use the second (Archer et al, 2010; Butler et al, 2007; Grisso et al, 2001; Nordness et al, 2002), this study, as well as a recent Australian study (Stathis et al, 2008) relying on samples dating from 2005 to 2010, found Alcohol/Drug Use as being the most highly endorsed subscale.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, similar to other recent studies (Aalsma et al, 2011; Archer et al, 2004; Archer et al, 2010; Grande et al, 2012; Grisso et al, 2001; Nordness et al, 2002; Stewart & Trupin, 2003), mean scores were higher for females than males on all subscales except thought disturbance (male only). While prior studies using samples dating from 2000 to 2006 found the Angry/Irritable subscale to be the most highly endorsed subscale with Alcohol/Drug Use the second (Archer et al, 2010; Butler et al, 2007; Grisso et al, 2001; Nordness et al, 2002), this study, as well as a recent Australian study (Stathis et al, 2008) relying on samples dating from 2005 to 2010, found Alcohol/Drug Use as being the most highly endorsed subscale.…”
Section: Discussionsupporting
confidence: 90%
“…However, due to the high amount of variability of the data as indicated by each scale's associated standard deviation, the study supports the previous findings that a high percentage of incarcerated youth qualify for a mental health disorder (Gretton & Clift, 2011;Nordness et al, 2002;Stathis et al, 2008;Stewart & Trupin, 2003), further suggesting that the MAYSI-2 accurately detects potential pathology. Also, similar to other recent studies (Aalsma et al, 2011;Archer et al, 2004;Archer et al, 2010;Grande et al, 2012;Grisso et al, 2001;Nordness et al, 2002;Stewart & Trupin, 2003), mean scores were higher for females than males on all subscales except thought disturbance (male only). While prior studies using samples dating from 2000 to 2006 found the Angry/Irritable subscale to be the most highly endorsed subscale with Alcohol/Drug Use the second (Archer et al, 2010;Butler et al, 2007;Grisso et al, 2001;Nordness et al, 2002), this study, as well as a recent Australian study (Stathis et al, 2008) relying on samples dating from 2005 to 2010, found Alcohol/Drug Use as being the most highly endorsed subscale.…”
Section: Discussionsupporting
confidence: 90%
“…It is linked to a computerized physician order entry system 30 . The RMRS is frequently used to assess actual practice patterns through secondary-data research 31,32 .…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…Justice-involved youth report elevated rates of mental health problems [3][4][5][6], substance misuse [7][8][9][10][11][12][13][14][15][16][17][18][19][20], and risky sexual activity [11,21], and compared to non-justice-involved peers, they are more likely to test positive for sexually transmitted infections (STIs) [22]. Incarceration during adolescence is associated with poor long-term outcomes [23][24][25][26][27][28], yet it is also an ideal opportunity to deliver intervention programs that address frequently co-occurring health problems. Unfortunately, few evidence-based programs (EBPs) exist for justice-involved adolescents, and those that have demonstrated efficacy go largely unused [29,30].…”
Section: Introductionmentioning
confidence: 99%